The Loop Electrosurgical Excision Procedure and Cone Conundrum: The Role of Cumulative Excised Depth in Predicting Preterm Birth - Panelli, Danielle M.; Wood, Rachel L.; Elias, Kevin M.; Growdon, Whitfield B.; Kaimal, Anjali J.; Feldman, Sarah; McElrath, Thomas F. (American Journal of Perinatology Reports, 2022)
Objective The objective was to determine factors associated with spontaneous preterm birth at less than 37 weeks in a cohort of patients who underwent a loop electrosurgical excision procedure (LEEP) or cone prior to pregnancy.Study Design This was a nested case-control study within a cohort of patients who underwent at least one LEEP or cone and had care for the next singleton pregnancy at either of two institutions between 1994 and 2014. Cases had spontaneous preterm birth at less than 37 weeks. Exposures included potential risk factors for preterm birth such as cumulative depth of excised cervix and time since excision. Reverse stepwise selection was used to identify the covariates for multivariable logistic regression.Results A total of 134 patients were included. Eighteen (13%) had a spontaneous preterm birth at less than 37 weeks. Median second-trimester cervical lengths were similar between those who delivered preterm and term (3.9-cm preterm and 3.6-cm term, p = 0.69). Patients who delivered preterm had a significantly greater median total excised depth of cervix (1.2 vs. 0.8 cm, p = 0.04). After adjustment for confounders, total excised depth remained significantly associated with preterm birth (adjusted odds ratio [aOR] = 2.2, 95% confidence interval [CI]: 1.3–3.8).Conclusion Total excised depth should be considered in addition to cervical length screening when managing subsequent pregnancies.Key Points
Keywords: cervical dysplasia; cervical excision; cervical length; cone biopsy; loop electrosurgical excision procedure; preterm birth